Early Excision And Skin Allograft Helps To Control Infection In Major Burn At Burn Unit Cipto Mangunkusumo Hospital - Natasha, Ratna Rayeni; Wardhana, Aditya (Lingkar Studi Bedah Plastik Foundation, 2012)
Backgrounds: Burns are systemic complex injuries following an exposure to thermal energy and can cause damage to the skin. Skin, as body cover, will protect the underlying tissue from infection, act as a thermo regulator and control the evaporations. The principle of burn therapy is to remove the necrotic tissue and to replace the function of the skin in the body by using a temporary cover with synthetic dressings or skin allograft. Skin allograft remains an ideal temporary cover, particularly when sufficient autograft skin is not available.Patients and Methods: We performed early excision and cover the wound with cadaver skin allograft in two patients suffered from major burn admitted to Cipto Mangunkusumo Hospital in 2012. We observed the wound clinically and monitored the leukocytes count to evaluate the rate of infection.Results: We observed four patients with major burn. Two patients treated with early excision and skin allograft has decreasing in exudates production, less bad odor in wound area, body temperature stable in normal value and also the decreasing leukocytes counts gradually. The results of wound area and body temperature in two patients treated conventionally are not much different from the initial wound and have high leukocytes count more than 10.000 in the majority of laboratory findings. The skin allograft can control the infection by suppressing the bacterial proliferation, promote epithelialization and prepare the wound better.Summary: Patient in this study treated with early excision and skin allograft has better outcome compared to patients treated conservatively.